A surface-modified nickel-titanium alloy material with anticancer and antibacterial effects, and its preparation method and application
By constructing a nickel-titanium layered double hydroxide film on the surface of nickel-titanium alloy and loading arsenic-containing drugs, catalytic activity is used to convert the arsenic valence state, the problem of poor antibacterial effect of nickel-titanium alloy stent in the treatment of gallbladder cancer is solved, and efficient killing and antibacterial effects on tumor cells is achieved, while ensuring low toxicity to normal cells.
Patent Information
- Application Number
- CN202210110969.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-01-29
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2042-01-29
AI Technical Summary
The existing medical nickel-titanium alloy stents have problems such as poor anti-bacterial effects and easy reobstruction when treating gallbladder cancer.
By constructing a nickel-titanium layered dihydroxide film on the surface of nickel-titanium alloy and loading arsenic-containing anionic drugs between the layers, the high catalytic activity of nickel is used to oxidize trivalent arsenic to pentavalent arsenic, preferentially release pentavalent arsenic in normal cellular environment, and at the same time, converting it into highly toxic trivalent arsenic through the action of glutathione in the tumor cell environment.
It has achieved significant inhibition of gallbladder cancer cells and excellent antibacterial ability to Staphylococcus aureus and E. coli, meeting the requirements of medical nickel-titanium alloy devices for cancer suppression and antibacterial ability, while maintaining low toxic side effects on normal cells.
Smart Images

Figure CN116549741B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a surface modified nickel-titanium alloy material with anticancer and antibacterial effects, a preparation method and application thereof, and belongs to the technical field of metal material surface modification. Background Art
[0002] Gallbladder cancer is a common cancer in the human bile duct. It is reported that the overall 5-year survival rate of gallbladder cancer is less than 30%, less than 20% in stage III, and about 3% in stage IV. In 2018, the International Agency for Research on Cancer (IARC) Globocan 2018 database estimated that deaths from gallbladder cancer accounted for 1.7% of all cancer deaths, with approximately 220,000 new cases diagnosed each year. In addition, gallbladder cancer is also characterized by hidden onset, rapid development, and poor prognosis. Currently, most (more than 90%) patients are diagnosed in the late stage, and most gallbladder cancer patients die of malignant obstruction. Nitinol stent implantation is a common method to relieve obstructive jaundice and is also the gold standard for prolonging patients' lives. However, nitinol stents are susceptible to tumor invasion and bacterial infection, resulting in a high re-obstruction rate. Drug-eluting stents (DESs) loaded with anti-tumor or antibacterial drugs are considered a solution to prevent in-stent restenosis, but have little clinical effect. This is because most commercially available DESs are derived from cardiovascular stents, and the main function of loaded drugs such as rapamycin, aspirin, and statins is to reduce inflammation and promote endothelialization, rather than killing bacteria and gallbladder tumor cells. Therefore, there is an urgent need for nickel-titanium alloy DES specifically for palliative treatment of gallbladder cancer. Summary of the invention
[0003] In order to solve the problem that the existing medical nickel-titanium alloy stents cannot inhibit cancer and fight bacteria, and are prone to cause obstruction of the medical devices prepared therefrom, a surface-modified nickel-titanium alloy material, a preparation method and an application thereof that can achieve cancer inhibition and fight bacteria are provided. The surface-modified nickel-titanium alloy can effectively regulate the biological behavior of cancer cells and bacteria. Cell proliferation experiments show that the modified nickel-titanium alloy has a significant inhibitory effect on the proliferation of gallbladder cancer GBC-SD cells. The bacterial plating results show that the surface-modified nickel-titanium alloy of the present invention exhibits excellent antibacterial ability against both Staphylococcus aureus and Escherichia coli. The above all indicate that the surface-modified nickel-titanium alloy of the present invention can meet the requirements of medical nickel-titanium alloy devices that come into contact with tumor tissues for the material's anti-cancer and antibacterial ability.
[0004] Here, in the first aspect, the present invention provides a surface-modified nickel-titanium alloy material with anticancer and antibacterial effects. The surface-modified nickel-titanium alloy material comprises a nickel-titanium layered double hydroxide film with a hydrotalcite-like structure and an arsenic-containing anion drug loaded between the layers; the surface-modified nickel-titanium alloy material undergoes an effective transformation of arsenic valence states in different microenvironments of tumor cells and normal cells, and has adaptively selected toxicity.
[0005] Preferably, the surface modified nickel-titanium alloy material exists in the form of low-toxic pentavalent arsenic in the normal cell microenvironment, and exists in the form of high-toxic trivalent arsenic in the tumor cell microenvironment.
[0006] Preferably, the high catalytic activity of nickel in the nickel-titanium layered double hydroxide causes at least a portion of the trivalent arsenic to be oxidized to pentavalent arsenic, prompting the surface-modified nickel-titanium alloy material to preferentially release pentavalent arsenic; the release of pentavalent arsenic is accelerated under the action of hydrogen ions in the tumor cell microenvironment, and the high concentration of glutathione in the tumor cell microenvironment further reduces the pentavalent arsenic to trivalent arsenic.
[0007] Preferably, the loading amount of the arsenic anion drug in the surface-modified nickel-titanium alloy material is less than 8%. Preferably, the loading amount of the arsenic anion drug in the surface-modified nickel-titanium alloy material is less than 7.33%.
[0008] The surface modification layer of the surface modified nickel-titanium alloy material of the present invention is composed of nickel-titanium layered double hydroxide loaded with arsenic-containing anion drugs. In the modified layer, due to the high catalytic activity of nickel in the nickel-titanium layered double hydroxide species, part of the highly toxic trivalent arsenic loaded is oxidized to low-toxic pentavalent arsenic. Specifically, the interlayer anions first undergo a transformation to their corresponding oxygen-containing acids, and then to the corresponding oxides. Since pentavalent arsenic has a relatively low binding energy, the constructed film preferentially releases pentavalent arsenic with less toxicity, while limiting the more toxic trivalent arsenic to the interlayer, which ensures the biosafety of the film in normal tissues. On the contrary, the acidic tumor environment promotes the degradation of LDHs and the hydrolysis of interlayer arsenates and arsenic-containing anion drugs (such as arsenite ions), which increases the release and accumulation of arsenic in the tumor environment. More importantly, the overexpression of GSH in tumor tissues further converts the low-toxic pentavalent arsenic into highly toxic trivalent arsenic, thereby exerting the highly toxic killing effect of trivalent arsenic. On the contrary, the low GSH concentration in normal tissues causes a small amount of released arsenic to exist only in the form of pentavalent arsenic with lower toxicity. The nickel element in LDH itself and the released arsenic element have a good killing effect on bacteria.
[0009] On the other hand, the present invention also provides a method for preparing the surface-modified nickel-titanium alloy material having anticancer and antibacterial effects as described in any one of the above. The preparation method comprises:
[0010] Step (1) generating a nickel-titanium layered double hydroxide film on the surface of the nickel-titanium alloy by hydrothermal treatment;
[0011] Step (2) pre-treating the nickel-titanium layered double hydroxide film by high temperature calcination to remove interlayer anions;
[0012] Step (3) carries out interlayer loading of arsenic anion drugs on the pretreated nickel-titanium layered double hydroxide film.
[0013] The principle of loading drugs on nickel-titanium layered double hydroxide thin films is that anions can be loaded between the layers of the layered double hydroxide by charge compensation. The anions in the original interlayer are removed by calcining at high temperature, and then the anion drugs are loaded between the layers. In simple terms, the arsenite anions of the arsenic anion drug replace the anions in the original layer (specifically carbonate ions and cyanate ions). Therefore, the preparation method of the present invention includes the step of removing interlayer anions.
[0014] Preferably, in step (1), the hydrothermal treatment process includes: adding nickel-titanium alloy and a precursor solution containing a nickel source and a titanium source into a reactor, the filling degree of the reactor is 40% to 80%, the reaction temperature is 50° C. to 150° C., and the reaction time is 10 h to 30 h.
[0015] Preferably, the precursor solution comprises: NiCl4·6H2O concentration of 0.01M to 0.5M, the hydrothermal medium is ultrapure water, the urea concentration is 0.5M to 5M, the hydrochloric acid concentration is 6M to 15M, and the TiCl4 concentration is 5M to 15M.
[0016] Preferably, in step (2), the calcination temperature is 250°C to 450°C, the heating rate is 5°C / min to 10°C / min, and the holding time is 1h to 3h.
[0017] Preferably, in step (3), the pretreated nickel-titanium layered double hydroxide film is soaked in an aqueous solution containing arsenic anion drugs for a period of time, taken out, washed and dried to obtain the surface-modified nickel-titanium alloy material with anticancer and antibacterial effects.
[0018] In a third aspect, the present invention also provides the use of the surface-modified nickel-titanium alloy material with anticancer and antibacterial effects as described in any of the above items in medical nickel-titanium alloy devices that come into contact with tumor tissue. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 The scanning electron microscope morphology images obtained after treatment in Examples 1, 2, 3, 4, 5, and 6. In the figure, Ni-Ti refers to the untreated sample after pickling, LDH refers to the sample after hydrothermal treatment, CLDH refers to the sample after LDH calcination treatment, and CLDH-5, CLDH-25, and CLDH-100 refer to the samples after CLDH is loaded with different concentrations of sodium arsenite.
[0020] Figure 2It is an X-ray photoelectron spectroscopy analysis diagram and a local magnified diagram after treatment in Examples 2, 3, 4, and 5. In the figure, Ni-Ti refers to the untreated sample after pickling, LDH refers to the sample after hydrothermal treatment, CLDH refers to the sample after LDH calcination treatment, and CLDH-5, CLDH-25, and CLDH-100 refer to the samples after CLDH is loaded with different concentrations of sodium arsenite. The curves in the figure are Ni-Ti, LDH, CLDH, CLDH-5, CLDH-25, and CLDH-100 from top to bottom.
[0021] Figure 3 It refers to the X-ray photoelectron spectroscopy analysis (arsenic high power spectrum) of the samples treated by Examples 4, 5 and 6. The sample in the figure is the sample after CLDH is loaded with 5 mM sodium arsenite, namely CLDH-5.
[0022] Figure 4 It is the simulation calculation result of the binding energy of the sample after treatment in Example 4. The calculation model established in the figure is the sample after CLDH is loaded with 5mM sodium arsenite, that is, CLDH-5. a, b, c, and d in the figure are the cohesive energy of trivalent arsenic anion intercalation, the intercalation model of arsenic trioxide, the cohesive energy of pentavalent arsenic anion intercalation, and the intercalation model of arsenic pentoxide, respectively.
[0023] Figure 5 The liquid chromatograms of arsenic after the samples treated in Example 4 were immersed in glutathione (GSH) solutions of different concentrations. The samples in the figure are samples after CLDH was loaded with 5mM sodium arsenite, i.e., CLDH-5. The GSH concentration of a is 0.1mM, the GSH concentration of b is 1mM, and the GSH concentration of c is 10mM.
[0024] Figure 6 The results are the proliferation results of gallbladder cancer cells (GBC-SD) and normal human gallbladder epithelial cells (HGBEC) planted on the surface of the samples obtained after treatment in Examples 1, 2, 3, 4, 5, and 6. In the figure, Ni-Ti refers to the untreated sample after acid washing, LDH refers to the sample after hydrothermal treatment, CLDH refers to the sample after LDH calcination treatment, and CLDH-5, CLDH-25, and CLDH-100 refer to the samples after CLDH is loaded with different concentrations of sodium arsenite.
[0025] Figure 7 The results of 24h bacterial plating of Staphylococcus aureus and Escherichia coli on the sample surface after treatment in Examples 1, 2, 3, 4, 5, and 6. In the figure, Ni-Ti refers to the sample without treatment after acid washing, LDH refers to the sample after hydrothermal treatment, CLDH refers to the sample after LDH calcination treatment, and CLDH-5, CLDH-25, and CLDH-100 refer to the samples after CLDH is loaded with different concentrations of sodium arsenite. DETAILED DESCRIPTION
[0026] The present invention is further described by the following embodiments. It should be understood that the following embodiments are only used to illustrate the present invention, but not to limit the present invention. In the absence of special instructions, each percentage content refers to the percentage content by mass.
[0027] In order to solve the problem that the existing medical nickel-titanium alloy stent materials have poor anti-cancer effect and poor antibacterial performance, the present invention discloses a surface-modified nickel-titanium alloy material with anti-cancer and antibacterial effects and a surface modification method thereof. For this purpose, the present invention constructs an arsenic-containing nickel-titanium layered double hydroxide (Ni-Ti LDHs) film on the surface of the nickel-titanium alloy. LDHs are composed of positively charged edge-sharing octahedral coordinated metal hydroxide layers, sandwiched between charge-compensated interlayer anions, and have an optional dissolution effect. The film can maintain a highly toxic trivalent arsenic state in gallbladder cancer tissue, and is effectively converted into less harmful pentavalent arsenic when cultured with normal cells. It has been verified that this preferred selectivity and microenvironment-responsive anti-tumor effect are related to the specific chemical composition and crystal structure of Ni-Ti LDHs. It is explained here that the high catalytic activity of nickel in the nickel-titanium layered double hydroxide allows part of the loaded highly toxic trivalent arsenic to be oxidized to low-toxic pentavalent arsenic. That is, the loaded arsenic contains both pentavalent arsenic and trivalent arsenic. The ratio of trivalent arsenic to pentavalent arsenic is preferably 3:1.
[0028] The nickel-titanium layered double hydroxide is formed in situ on the surface of nickel-titanium alloy. Moreover, as the loading amount of arsenic anion drugs increases, the toxicity of nickel-titanium layered double hydroxide to tumor cells increases further, while the toxic side effects to normal cells remain low. This indicates that the difference in toxicity is caused by the change in arsenic valence state caused by the different microenvironments of the two cells.
[0029] In summary, in the present invention, arsenic anion drugs such as arsenite are used as compensating ions to enable them to enter the interlayer of LDHs for arsenic loading. As a layered double hydroxide, the high nickel content in Ni-Ti LDH gives it a strong ability to catalyze redox reactions, which allows a small portion of the loaded trivalent arsenic ions to be oxidized to pentavalent arsenic ions. Due to the difference in the microenvironment of normal cells and tumor cells, there are differences in the released arsenic elements, which are specifically manifested as low-toxic pentavalent arsenic in normal cells and highly toxic trivalent arsenic in tumor cells. And the nickel element in LDH itself and the released arsenic element have good killing effects on bacteria. A series of in vitro and in vivo experiments verified the high biocompatibility, selective anti-tumor and antibacterial effects of the constructed platform, providing a new prototype for the design of DES for the treatment of gallbladder cancer.
[0030] Chinese patent CN 105343941A discloses a surface-modified biomedical nickel-titanium alloy and its preparation method and application, wherein the main component of the surface of the surface-modified nickel-titanium alloy material is selenium-doped nickel-titanium layered double hydroxide. Its selective anti-cancer and anti-bacterial properties are realized by utilizing the different tolerances of cancer cells and normal cells to selenium content. Specifically, tumor cells have a low tolerance to selenium, while normal cells have a high tolerance to selenium. Therefore, by regulating the amount of selenium loading, the released selenium content does not cause damage to normal cells, while having a certain degree of killing effect on tumor cells. Therefore, this selectivity is achieved by regulating the amount of drug release and utilizing the difference in drug sensitivity of the two cells. As for the antibacterial effect, it is derived from the fact that nickel and selenium elements themselves have certain antibacterial effects.
[0031] Chinese patent CN 105536077A discloses a nickel-titanium alloy drug-carrying material, which selectively inhibits cancer in the following way: the nickel-titanium layered double hydroxide layer first bonds with sodium polystyrene sulfonate, and then utilizes the electrostatic interaction between sodium polystyrene sulfonate and the DOX drug to achieve drug loading. Because the tumor microenvironment is acidic, the chemical bond between the nickel-titanium layered double hydroxide layer and sodium polystyrene sulfonate is unstable and easy to break under acidic conditions, so the DOX drug connected thereto will also be released. The normal cell microenvironment is neutral or slightly alkaline, and the chemical bond between the nickel-titanium layered double hydroxide layer and sodium polystyrene sulfonate is relatively stable, so the DOX drug will not be released or the release amount is low. Therefore, this selectivity is achieved by the difference in the pH value between the two cell microenvironments, which leads to the difference in the amount of drug released.
[0032] The design concept of the selective anti-cancer and antibacterial of the present invention is: a large number of studies have shown that trivalent arsenic has a higher toxicity, while pentavalent arsenic has a lower toxicity. On this basis, the present invention designs a nickel-titanium layered double hydroxide layer loaded with arsenic, which will preferentially release low-toxic pentavalent arsenic due to the difference in binding energy. However, there is a high concentration of GSH in the tumor microenvironment, so that the low-toxic pentavalent arsenic is further converted into highly toxic trivalent arsenic in the tumor tissue. At the same time, another feature of the tumor microenvironment, that is, the acidic microenvironment, can also accelerate the release of arsenic, so that the accumulation of arsenic in the tumor tissue increases while it also acts in a highly toxic trivalent form, which has a "two-pronged" synergistic effect. For normal cells, due to the low GSH concentration in their microenvironment, which is about one-tenth to several tens of tenths of that in the tumor microenvironment, arsenic exists in a low-toxic pentavalent form, and the neutral or alkaline microenvironment of normal cells does not accelerate the release of arsenic, so the released arsenic has less toxic side effects on normal cells, and has a "double" protection function. Therefore, the selective anti-cancer effect of this experiment not only utilizes the toxicity differences caused by different drug forms and different contents, but also utilizes the differences in pH and GSH expression in the two cell microenvironments to achieve the selective effect. Compared with the above-mentioned patents CN 105343941A and CN105536077A, the selectivity embodied in the present invention is more comprehensive and rich. As for the antibacterial effect, it comes from the joint action of nickel ions and arsenic.
[0033] The present invention also provides a surface modification method for medical nickel-titanium alloy materials. Specifically, a layer of layered double metal hydroxide film is first constructed on the surface of the nickel-titanium alloy by hydrothermal treatment, and then the synthesized film is pretreated by high-temperature calcination to remove interlayer anions, and then the arsenic anion drug is loaded, thereby realizing the surface modification of the nickel-titanium alloy. The preparation method of the present invention is simple and easy, low in cost, good in stability, and high in safety.
[0034] A layer of layered double hydroxide film is generated on the surface of nickel-titanium alloy by hydrothermal treatment. The hydrothermal medium is ultrapure water. The concentration of NiCl4·6H2O added to the precursor solution of the hydrothermal treatment is 0.01-0.5M, the concentration of urea is 0.5-5M, the concentration of hydrochloric acid is 6-15M, and the concentration of TiCl4 added is 5-15M. As an example, the added volume is 1-5mL. In some embodiments, the reaction time is 50-150°C, the reaction time is 10-30h, and the filling degree of the reactor is 40%-80%.
[0035] The interlayer anions are removed by pretreatment using a high temperature calcination method. The calcination temperature is 250°C to 450°C, the heating rate is 5°C / min to 10°C / min, and the holding time is 1h to 3h.
[0036] The film is then loaded with a special anticancer drug - an arsenic-containing anion drug. The means of loading the drug is not limited, and a commonly used method in the art can be used. In a specific embodiment of the present invention, the pretreated nickel-titanium layered double hydroxide film is soaked in an aqueous solution of an arsenic-containing anion drug for a period of time, then taken out, washed and dried to obtain the surface-modified nickel-titanium alloy material with anticancer and antibacterial effects. Arsenic-containing anion drugs include but are not limited to sodium arsenate, potassium arsenite, and potassium arsenate.
[0037] The surface of the material modified by the present invention is composed of nickel-titanium layered double hydroxide. In addition, due to the high catalytic activity of nickel in nickel-titanium layered double hydroxide, the subsequent drug-loading treatment oxidizes part of the highly toxic trivalent arsenic loaded into low-toxic pentavalent arsenic. Binding energy calculations show that the drug-loaded film preferentially releases low-toxic pentavalent arsenic, which can ensure the low toxicity of the drug-loaded film to normal gallbladder cells (HGBEC). At the same time, a large amount of hydrogen ions in the microenvironment of gallbladder tumor cells (GBC-SD) will accelerate the release of pentavalent arsenic, which is further reduced to highly toxic trivalent arsenic by high concentrations of glutathione (GSH) in the environment, increasing the accumulation of arsenic in the tumor environment while being able to exert the high toxicity of trivalent arsenic to gallbladder tumor tissue. At the same time, the modified nickel-titanium alloy exhibits good antibacterial ability. The results of bacterial plating show that the modified material has improved inhibition of Staphylococcus aureus and Escherichia coli. The invention endows the nickel-titanium alloy stent with anticancer and antibacterial effects, is a drug-eluting stent with good application prospects, and can be widely used in the surface modification of nickel-titanium alloy medical devices in contact with tumor tissues.
[0038] The following further examples are given to illustrate the present invention in detail. It should also be understood that the following examples are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made by those skilled in the art based on the above content of the present invention belong to the scope of protection of the present invention. The specific process parameters and the like in the following examples are also only examples within a suitable range, that is, those skilled in the art can make a selection within a suitable range through the description herein, and are not limited to the specific values exemplified below.
[0039] Example 1
[0040] A nickel-titanium disc with a diameter of 12 mm and a thickness of 2 mm was ultrasonically cleaned 3 times with an acid wash solution (volume ratio of HF:HNO3:H2O = 1:5:4), each cleaning time was 5 minutes, and the amount of acid wash solution for each nickel-titanium disc was 5 mL. After cleaning, it was ultrasonically cleaned twice with ultrapure water, each cleaning time was 5 minutes, and then dried in an oven at 60°C. The obtained sample was marked as Ni-Ti.
[0041] Figure 1The scanning electron microscope morphology of the Ni-Ti sample obtained after the treatment in this embodiment is shown. It can be seen from the figure that the surface of the Ni-Ti sample is smooth after the treatment. Figure 2 The X-ray photoelectron spectroscopy analysis diagram of the Ni-Ti sample obtained after the treatment in this embodiment is shown. It can be seen from the figure that the main components of the surface of the sample after the treatment are nickel, titanium and oxygen.
[0042] Example 2
[0043] Add 1.426g NiCl4·6H2O and 6.5g urea to 100mL ultrapure water, stir well and put in a 4℃ refrigerator for precooling for 0.5 hours, then add 0.25mL hydrochloric acid and 0.25mL TiCl4 in an ice bath environment, stir well and put in a 4℃ refrigerator as a precursor solution. During hydrothermal treatment, add nickel titanium discs and precursor solution to the reactor, dilute the precursor solution by 20 times, and use 5mL diluted precursor solution for each nickel titanium disc, reaction temperature 120℃, reaction time 24h. The obtained sample is labeled as LDH.
[0044] Figure 1 The SEM morphology of the LDH sample obtained after the treatment in this embodiment is shown. It can be seen from the figure that the surface of the LDH sample after the treatment presents a nanosheet structure, and the length of the nanosheet is about 2 μm and the thickness is about 30 nm. Figure 2 The X-ray photoelectron spectroscopy analysis diagram of the LDH sample obtained after treatment in this embodiment is shown. It can be seen from the figure that the main components of the surface of the sample after treatment are nickel, titanium and oxygen.
[0045] Example 3
[0046] The LDH sample prepared in Example 2 was calcined at 250°C, a heating rate of 5°C / min, and a holding time of 2h. After cooling naturally to room temperature, it was placed in ultrapure water for 24h and then taken out and dried. The obtained sample was labeled as CLDH.
[0047] Figure 1 The scanning electron microscope morphology of the CLDH sample obtained after treatment in this embodiment is shown. It can be seen from the figure that the morphology of the sample after treatment is not significantly different from that of the LDH sample, and the surface presents a nanosheet structure with a length of about 2 μm and a thickness of about 30 nm. Figure 2 The X-ray photoelectron spectroscopy analysis diagram of the CLDH sample obtained after treatment in this embodiment is shown. It can be seen from the figure that the main components of the surface of the treated sample are nickel, titanium and oxygen, and there is no obvious difference in the types of elements compared with the untreated Ni-Ti sample and LDH sample.
[0048] Example 4
[0049] The CLDH sample prepared in Example 3 was placed in a 5 mM sodium arsenite solution for 24 hours, then washed three times with ultrapure water and dried at 60° C. The obtained sample was labeled as CLDH-5.
[0050] Figure 1 The scanning electron microscope morphology of the CLDH-5 sample obtained after treatment in this embodiment is shown. It can be seen from the figure that the morphology of the sample after treatment is not significantly different from that of the LDH and CLDH samples, and the surface presents a nanosheet structure with a length of about 2 μm and a thickness of about 30 nm. Figure 2 The X-ray photoelectron spectroscopy analysis diagram of the CLDH-5 sample obtained after treatment in this embodiment is shown. It can be seen from the figure that the main components of the surface of the sample after treatment are nickel, titanium, oxygen and arsenic, indicating the successful loading of arsenic element. Figure 3 The X-ray photoelectron spectroscopy analysis diagram (arsenic high-power spectrum) obtained after the CLDH-5 sample was treated in this embodiment is shown. It can be seen from the figure that the loaded arsenic contains both pentavalent arsenic and trivalent arsenic, wherein the ratio of trivalent arsenic to pentavalent arsenic is about 3:1. This is mainly due to the high nickel content. Ni-Ti LDH has a strong catalytic activity for redox reactions, and divalent nickel easily loses electrons and becomes trivalent nickel with high oxidizability (reaction 1). Trivalent nickel is unstable and can react with water in the environment to produce hydroxyl radicals with high oxidizing properties. These hydroxyl radicals further react with arsenic ions loaded between the LDH layers to produce pentavalent arsenic (reactions 2 and 3). The above reaction can also be carried out in the opposite direction, resulting in incomplete conversion of trivalent arsenic into pentavalent arsenic. The ratio of As(III) and As(V) is determined by the reaction constant, so a fixed ratio is maintained.
[0051]
[0052]
[0053]
[0054] Figure 4 The results of the sample binding energy simulation calculation after treatment in Example 4 are shown. The results show that the cohesive energy of the trivalent arsenic anion intercalation is 31.765 eV (see Figure 4 a), while the cohesive energy of pentavalent arsenic anion intercalation is 32.923e (see Figure 4 c). This indicates that both trivalent and pentavalent arsenic can be easily absorbed by the CLDH sample, which has been confirmed by the XPS results. In addition, pentavalent arsenic is more easily incorporated into the CLDH sample than trivalent arsenic in pursuit of a more stable structure. The trivalent arsenic ion then hydrolyzes to produce arsenite, which then decomposes into arsenic trioxide (Reaction 4 and Reaction 5). Similarly, the anion of pentavalent arsenic also undergoes similar reactions (Reaction 6 and Reaction 7). To this end, we continue to establish arsenic trioxide ( Figure 4 b) and arsenic pentoxide ( Figure 4 d) Intercalation model was used to calculate its cohesive force. The results showed that the cohesive force of LDHs inserted into trivalent arsenic oxide was 17.985 eV, and the cohesive force of LDHs inserted into pentavalent arsenic oxide was 15.547 eV, both of which were much lower than ionic LDHs. In addition, the cohesive force of LDHs loaded with pentavalent arsenic oxide was lower than that of LDHs loaded with trivalent arsenic oxide. Therefore, in normal physiological environment, samples will selectively release pentavalent arsenic preferentially, which can be seen from Figure 5 The experimental results can also be further verified.
[0055]
[0056]
[0057]
[0058]
[0059] Figure 5 The liquid chromatogram of arsenic after the CLDH-5 sample treated in this embodiment is immersed in glutathione (GSH) solutions of different concentrations is shown. It can be seen from the figure that when the GSH concentration is 0mM, that is, the arsenic released under normal physiological conditions is all pentavalent arsenic, which also verifies the above results. When the GSH concentration increases to 0.1mM, a small amount of trivalent arsenic appears (the average value is about 5%). When the GSH concentration increases to 10mM, it is found that all pentavalent arsenic in the environment is converted into trivalent arsenic. This is mainly because the released pentavalent arsenic has a certain oxidizing property and can undergo redox reaction with GSH to become trivalent. The toxicity of trivalent arsenic is much higher than that of pentavalent arsenic. At the same time, a large number of studies have shown that there is a phenomenon of overexpression of GSH concentration in the tumor environment, with a concentration as high as 10mM, which is dozens of times the GSH concentration in the normal cell environment. Therefore, the above results collectively indicate that this modification method can achieve the conversion of low-toxic pentavalent arsenic to highly toxic trivalent arsenic in tumor tissue, thereby achieving highly toxic killing of tumor tissue, while a small amount of low-toxic pentavalent arsenic exists in normal cells, thus ensuring low toxic side effects on normal tissues.
[0060] Example 5
[0061] The sample prepared in Example 3 was placed in a 25 mM sodium arsenite solution for 24 hours, then washed three times with ultrapure water and dried at 60° C. The obtained sample was labeled as CLDH-25.
[0062] Figure 1The scanning electron microscope morphology of the CLDH-25 sample obtained after treatment in this embodiment is shown. It can be seen from the figure that the morphology of the sample after treatment is not significantly different from that of the LDH and CLDH samples, and the surface presents a nanosheet structure with a length of about 2 μm and a thickness of about 30 nm. Figure 2 The X-ray photoelectron spectroscopy analysis diagram of the CLDH-25 sample obtained after treatment in this embodiment is shown. It can be seen from the figure that the main components of the surface of the sample after treatment are nickel, titanium, oxygen and arsenic, indicating the successful loading of arsenic element. Figure 3 The X-ray photoelectron spectroscopy analysis diagram (arsenic high-power spectrum) of the CLDH-25 sample obtained after treatment in this embodiment is shown. It can be seen from the figure that the loaded arsenic contains both pentavalent arsenic and trivalent arsenic, wherein the ratio of trivalent arsenic to pentavalent arsenic is about 3:1. This is mainly because due to the high nickel content, Ni-Ti LDH has a strong catalytic activity for redox reactions, and divalent nickel easily loses electrons and becomes trivalent nickel with high oxidizability (reaction 1). Trivalent nickel is unstable and can react with water in the environment to produce hydroxyl radicals with high oxidizing properties, which further react with arsenic ions loaded between the LDH layers to produce pentavalent arsenic (reactions 2 and 3). The above reaction can also be carried out in the opposite direction, resulting in incomplete conversion of trivalent arsenic into pentavalent arsenic. The ratio of As(III) and As(V) is determined by the reaction constant, so a fixed ratio is maintained.
[0063]
[0064]
[0065]
[0066] Example 6
[0067] The sample prepared in Example 3 was placed in a 100 mM sodium arsenite solution for 24 hours, then washed three times with ultrapure water and dried at 60° C. The obtained sample was labeled as CLDH-100.
[0068] Figure 1 The scanning electron microscope morphology of the CLDH-100 sample obtained after treatment in this embodiment is shown. It can be seen from the figure that the morphology of the sample after treatment is not significantly different from that of the LDH and CLDH samples, and the surface presents a nanosheet structure with a length of about 2 μm and a thickness of about 30 nm. Figure 2 The X-ray photoelectron spectroscopy analysis diagram of the CLDH-100 sample obtained after treatment in this example is shown. It can be seen from the figure that the main components of the surface of the sample after treatment are nickel, titanium, oxygen and arsenic, indicating that the arsenic element is successfully loaded. Figure 3The X-ray photoelectron spectroscopy analysis diagram (arsenic high-power spectrum) of the CLDH-100 sample obtained after treatment in this embodiment is shown. It can be seen from the figure that the loaded arsenic contains both pentavalent arsenic and trivalent arsenic, wherein the ratio of trivalent arsenic to pentavalent arsenic is about 3:1. This is mainly because due to the high nickel content, Ni-Ti LDH has a strong catalytic activity for redox reactions, and divalent nickel easily loses electrons and becomes trivalent nickel with high oxidizability (reaction 1). Trivalent nickel is unstable and can react with water in the environment to produce hydroxyl radicals with high oxidizing properties, which further react with arsenic ions loaded between the LDH layers to produce pentavalent arsenic (reactions 2 and 3). The above reaction can also be carried out in the opposite direction, resulting in incomplete conversion of trivalent arsenic into pentavalent arsenic. The ratio of As(III) and As(V) is determined by the reaction constant, so a fixed ratio is maintained.
[0069]
[0070]
[0071]
[0072] Example 7
[0073] In vitro culture experiments of human gallbladder cancer cells GBC-SD and normal human gallbladder epithelial cells were used to evaluate the effects of the untreated nickel-titanium alloy (Example 1) and the nickel-titanium materials modified by the above Examples 2, 3, 4, 5, and 6 on the activity of cancer cells. Alamar Blue was used to detect the activity of the nickel-titanium alloy. TM , AbD serotec Ltd, UK) kit was used to detect the proliferation of cells on the surface of the material. The method is as follows:
[0074] 1) Place the sample sterilized with 75% ethanol in a 24-well culture plate and drip 1 mL of 5×10 4 cell / mL cell suspension;
[0075] 2) Place the cell culture plate in a cell culture incubator with 5% CO2 saturated humidity and incubate at 36.5°C for 18 hours;
[0076] 3) Remove the cell culture medium, wash the sample surface with PBS, move the sample to a new 24-well plate, and continue culturing in an incubator;
[0077] 4) After 1, 4 and 7 days of cell culture, the original culture medium was removed and a 5% volume fraction of Alamar Blue was added. TM ) new culture medium with dye solution, place the culture plate in an incubator and culture for 2 h, then take out 100 μL of culture medium from each well and put it into a 96-well plate;
[0078] 5) The absorbance of each well at wavelengths of 560 nm and 590 nm was measured using an ELISA reader (BIO-TEK, ELX800).
[0079] Figure 6 The left figure is the cell proliferation result diagram of GBC-SD cancer cells planted after treatment in Examples 1, 2, 3, 4, 5, and 6. It can be seen from the figure that the surface sample of the Ni-Ti alloy sample is in good growth state, and the number of cells has a significant increasing trend within 7 days. The LDH and CLDH sample cancer cells have a certain inhibitory effect, but the cancer cells are not completely killed, and the number of cancer cells in the two groups of samples has an increasing trend over time, indicating that the anti-cancer effect of the two groups of samples is weak. The three groups of samples (CLDH-5, CLDH-25 and CLDH-100) treated with arsenic have a strong killing effect on cancer cells. At 4 days, there are almost no surviving cancer cells on the surface of the three groups of samples, and the number of cancer cells does not increase at 7 days. It shows that after arsenic treatment, the anti-tumor effect of the sample is further enhanced. Figure 6 The right figure is a cell proliferation result diagram after normal human gallbladder epithelial cells (HGBEC) were implanted after treatment in Examples 1, 2, 3, 4, 5, and 6. Compared with cancer cells, the arsenic-loaded samples also have certain early toxic side effects on normal cells, but the toxic side effects are smaller. At 7 days, it can be found that the normal cells indicated by the arsenic-loaded samples have increased significantly compared with 1 day and 4 days, which indicates that the samples have less toxic side effects on normal cells while maintaining efficient killing of tumor cells. The reason for the above phenomenon is that the difference in the two cell microenvironments leads to different arsenic valence states, which in turn produces different toxicity differences.
[0080] Example 8
[0081] The samples treated by the above examples 1, 2, 3, 4, 5, and 6 were subjected to antibacterial experiments on Staphylococcus aureus and Escherichia coli: the samples were sterilized under ultraviolet light for 6 h, and the concentration of 10 7 CFU / mL of bacterial droplets were placed on the sterilized sample surface (0.06mL / cm 2 ), and then place the sample with the bacterial solution in a 37℃ constant temperature incubator for 24 hours. Take out the sample after 24 hours of incubation, dilute the bacterial solution in multiple ratios, and inoculate it on an agar plate containing culture medium. The inoculated agar plate is placed in a 37℃ constant temperature incubator for 16 hours. After 16 hours of incubation, take out the agar plate and count the number of live bacteria.
[0082] Figure 7 The left picture shows the results of the plate coating experiment after the sample was inoculated with Staphylococcus aureus. As can be seen from the picture, only a small amount of bacteria can be seen on the surface of the agar plate of the arsenic-loaded sample group, indicating that the arsenic-loaded sample group has good antibacterial ability against Staphylococcus aureus. Figure 7The right picture is the result of the plate coating experiment after the sample was inoculated with E. coli. As can be seen from the picture, only a small amount of bacteria can be seen on the surface of the agar plate of the arsenic-loaded sample group, indicating that the arsenic-loaded sample group has good antibacterial ability against E. coli.
[0083] Industrial applicability: The present invention endows nickel-titanium alloy with selective anticancer and antibacterial effects, and can be widely used in the surface modification of nickel-titanium alloy medical devices in contact with tumor tissues.
Claims
1. A method for preparing a surface-modified nickel-titanium alloy material having anticancer and antibacterial effects, characterized in that: The preparation method comprises: Step (1) generates a nickel-titanium layered double hydroxide film on the surface of the nickel-titanium alloy by hydrothermal treatment; in step (1), the hydrothermal treatment process comprises: adding the nickel-titanium alloy and a precursor solution containing a nickel source and a titanium source into a reaction kettle, the filling degree of the reaction kettle is 40% to 80%, the reaction temperature is 50° C. to 150° C., and the reaction time is 10 h to 30 h; the composition of the precursor solution is: NiCl4·6H2O concentration is 0.01 M to 0.5 M, the hydrothermal medium is ultrapure water, the urea concentration is 0.5 M to 5 M, the hydrochloric acid concentration is 6 M to 15 M, and the TiCl4 concentration is 5 M to 15 M; Step (2) pre-treats the nickel-titanium layered double hydroxide film by high-temperature calcination to remove interlayer anions of the nickel-titanium layered double hydroxide film; in step (2), the calcination temperature is 250°C to 450°C, the heating rate is 5°C / min to 10°C / min, and the holding time is 1h to 3h; step (3) loads the pre-treated nickel-titanium layered double hydroxide film with an arsenic anion drug so that the arsenite anions of the arsenic anion drug replace the anions in the original layer; in step (3), the pre-treated nickel-titanium layered double hydroxide film is soaked in an arsenic anion drug aqueous solution for 24 hours, taken out, washed and dried to obtain the surface-modified nickel-titanium alloy material with anticancer and antibacterial effects.
2. A surface-modified nickel-titanium alloy material having anticancer and antibacterial effects obtained by the preparation method according to claim 1, characterized in that: The surface modified nickel-titanium alloy material comprises a nickel-titanium layered double hydroxide film with a hydrotalcite-like structure and an arsenic-containing anion drug loaded between the layers; the surface modified nickel-titanium alloy material undergoes an effective transformation of arsenic valence states in different microenvironments of tumor cells and normal cells, and has adaptively selected toxicity.
3. The surface modified nickel-titanium alloy material according to claim 2, characterized in that: The surface modified nickel-titanium alloy material exists in the form of low-toxic pentavalent arsenic in the normal cell microenvironment, and exists in the form of high-toxic trivalent arsenic in the tumor cell microenvironment.
4. The surface modified nickel-titanium alloy material according to claim 2 or 3, characterized in that: The high catalytic activity of nickel in nickel-titanium layered double hydroxide causes at least part of the trivalent arsenic to be oxidized to pentavalent arsenic, prompting the surface-modified nickel-titanium alloy material to preferentially release pentavalent arsenic; the release of pentavalent arsenic is accelerated under the action of hydrogen ions in the tumor cell microenvironment, and the high concentration of glutathione in the tumor cell microenvironment further reduces the pentavalent arsenic to trivalent arsenic.
5. The surface modified nickel-titanium alloy material according to claim 2, characterized in that: The loading amount of the arsenic-containing anion drug in the surface-modified nickel-titanium alloy material is less than 8%.
6. Use of the surface modified nickel-titanium alloy material with anticancer and antibacterial effects according to any one of claims 2 to 5 in the preparation of medical nickel-titanium alloy devices in contact with tumor tissue.
Citation Information
Patent Citations
Nickel-titanium alloy drug loading material and preparation method thereof
CN105536077A
Surface-modified biomedical nickel-titanium alloy as well as preparation method and application thereof
CN105343941A